PELAKSANAAN PENDIDIKAN LIFE SKILLS DALAM PROGRAM WIRAUSAHA SISWA KELAS XI SMA NEGERI 5 PALEMBANG - Verra Wulandari; Dewi Koryati; Fitriyanti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
The research titled the implementation of life skills education in entrepreneurship program class XI SMA Nergeri 5 Palembang. This research is descriptive research is research that reveals facts on the ground by observing observation, conducting interviews and documentation. The research variables are life skills education in the form of extracurricular activities student entrepreneurs. The research subjects a class student of XI SMA Negeri 5 Palembang and the entire team of experts are on the debriefing of 6 branches entrepreneurs. Observation data used to determine the implementation of life skills education in entrepreneurship program and documentation used for school files. This study has show that the implemntation of life skills education in entrepreneurship program in SMA Negeri 5 Palembang say well look a lot of students who enthusiastidally participated in debriefing entrepreneurs, students can develop the potential in students.